Channel-Inactivating Mutations and Their Revertant Mutants in the Envelope Protein of Infectious Bronchitis Virus - To, Janet (2017)
It has been shown previously in the severe acute respiratory syndrome coronavirus (SARS-CoV) that two point mutations, N15A and V25F, in the transmembrane domain (TMD) of the envelope (E) protein abolished channel activity and led to in vivo attenuation. Pathogenicity was recovered in mutants that also regained E protein channel activity. In particular, V25F was rapidly compensated by changes at multiple V25F-facing TMD residues located on a neighboring monomer, consistent with a recovery of oligomerization. Here, we show using infected cells that the same mutations, T16A and A26F, in the gamma-CoV infectious bronchitis virus (IBV) lead to, in principle, similar results. However, IBV E A26F did not abolish oligomer formation and was compensated by mutations at N- and C-terminal extramembrane domains (EMDs). The C-terminal EMD mutations clustered along an insertion sequence specific to gamma-CoVs. Nuclear magnetic resonance data are consistent with the presence of only one TMD in IBV E, suggesting that recovery of channel activity and fitness in these IBV E revertant mutants is through an allosteric interaction between EMDs and TMD. The present results are important for the development of IBV live attenuated vaccines when channel-inactivating mutations are introduced in the E protein.